The codification of medical legislation in Ukraine: the question of the formulation of the problem - R. O. Stefanchuk; A. O. Yanchuk; M. M. Stefanchuk; M. O. Stefanchuk (Zaporozhye State Medical University, 2018)
The purpose of the research is to study and propose an integrated approach to the formation of legal health policy. National medical law is not systemic. Obsolete, duplicate and contradictory legal acts of varying legal force, excessive number of subordinate ministerial and departmental acts require the systematization of medical legislation, the creation of a coherent, logical and intra-contradictory system. It is necessary to combine the efforts and knowledge of lawyers and doctors to create an appropriate viable regulatory framework and improve the efficiency and quality of the law-making process. When developing its own legal and regulatory framework, it is necessary to take into account the international legal standards in the field of health protection, the experience of foreign countries in medical legislation, as well as national peculiarities, traditions and realities. Codification is a special and the most perfect and highest form of systematization of legislation. That is a streamlining of the legislative material, which is aimed at processing by eliminating repetitions, contradictions, filling gaps, transforming the nature and direction of the material, to the maximum extent provided by internal coherence, integrity, consistency and completeness of legal regulation of existing social relations. An urgent task is the creation of the Medical Code of Ukraine, which would meet the general standards of human rights and relevant international legal acts, which is dominated by directives and other acts of the World Health Organization.